Peran Organisasi Civil Society dan Belanja Program Penanggulangan TB (Tuberkulosis) di Indonesia: Studi Kasus PW (Persatuan Wilayah) Aisyiyah Aceh - Hasnur, Hanifah; Baharuddin, Dharina; Abdullah, Asnawi (Jurnal Ekonomi Kesehatan Indonesia, 2020)
The number of TB cases in Aceh has reached 8471 cases in 2018; 240 (2.8%) cases occurred among children. The real cases in the community were estimated higher than this figure. The success of TB control was influenced by many factors, including the roles of civil society organizations. This research was conducted to analyze the roles of civil society organizations in controlling TB cases in the community. A case study was conducted at PW Aisyiyah Aceh using an economic evaluation methodology for tracking expenditures for TB program activities (2011-2013) compared to the targets. The study showed that PW Aisyiyah has played significant roles in controlling cases of TB in Aceh through many community engagement activities included the TB Care Group; the TB Community activities, High-Risk Group Outreach activities; direct TB and MDR-TB patients monitoring; assisted and providing TB care information and networking to the community. PW Aisyiyah Aceh has spent budgets Rp. 844 million per year for TB program activities with 22.3% spent on promotive/preventive activities, 77.5% spent on indirect activities. To maximize and sustain the roles of PW Aisyiyah Aceh as a civil society organization in controlling the TB program, it is strongly suggested to explore other sources of budgets, including exploring the potential of collaborating Public-Private mix funding mechanism. PW Peran Organisasi Civil Society dan Belanja Program 62 Hasnur, Dharina, Abdullah Aisyiyah is also suggested to increase budget spending on promotive and preventive public health activities in addition to curative activities which have been the main mission of Aisyiyah community organizations in Indonesia.